Time use and options for retirement in Europe - Hannu Piekkola; Liisa Harmoinen (The Research Institute of the Finnish Economy (ETLA), 2003)
This paper examines the incentive effects of market and household work on retirement. This is accomplished by documenting the time use in market and household work in selected European countries. The assignment of an economic value to household work assumes substitutability of market and household work of some degree. With continuous lifetime patterns, household work may also replace market work after retirement. We construct replacement rates and option values that include the value of household work for 7 European countries. It is shown that the inclusion of household work in calculations on incentives makes the prospect of retiring more attractive, and that the calculation results correlate with actual retirement ages in Europe. Replacement rates are close to or exceed 100% when household work is accounted for. For men the increase in household work after withdrawing from the labour market is larger in relative terms (double on average). Therefore the effect of accounting for household work in the financial incentive to retire is greater for men. – Retirement ; Option value ; Time use ; Leisure ; Household work ; Option Value
Keywords: J26; J14; J22; J11; 330; Zeitallokation; Altersgrenze; Freizeit; Europa